2017
DOI: 10.1051/0004-6361/201730542
|View full text |Cite
|
Sign up to set email alerts
|

Strong H i Lyman-α variations from an 11 Gyr-old host star: a planetary origin?

Abstract: Kepler-444 provides a unique opportunity to probe the atmospheric composition and evolution of a compact system of exoplanets smaller than the Earth. Five planets transit this bright K star at close orbital distances, but they are too small for their putative lower atmosphere to be probed at optical/infrared wavelengths. We used the Space Telescope Imaging Spectrograph instrument onboard the Hubble Space Telescope to search for the signature of the planet's upper atmospheres at six independent epochs in the Ly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 65 publications
(79 reference statements)
6
45
0
Order By: Relevance
“…Wood et al 2005). This strengthens the trend noted in Bourrier et al (2017a) that M dwarfs show no self-reversal in their core, while K dwarfs sometimes show double-peaked profiles and G-type stars always do. K dwarfs might thus have transition regions, where the core of the Lyman-α line is formed (Vernazza et al 1981), that have intermediate structures in between those of G-type stars and M dwarfs.…”
Section: Reconstruction Of the Intrinsic Line Profilessupporting
confidence: 89%
“…Wood et al 2005). This strengthens the trend noted in Bourrier et al (2017a) that M dwarfs show no self-reversal in their core, while K dwarfs sometimes show double-peaked profiles and G-type stars always do. K dwarfs might thus have transition regions, where the core of the Lyman-α line is formed (Vernazza et al 1981), that have intermediate structures in between those of G-type stars and M dwarfs.…”
Section: Reconstruction Of the Intrinsic Line Profilessupporting
confidence: 89%
“…However, to date, no evidence for extended atmo-Article number, page 1 of 5 arXiv:2001.04532v2 [astro-ph.EP] 20 Jan 2020 A&A proofs: manuscript no. 37327 spheres has been found for planets smaller than Neptune, as nondetections were reported for the super-Earths 55 Cnc e (Ehrenreich et al 2012), HD 97658 b (Bourrier et al 2017c), GJ 1132 b (Waalkes et al 2019), and π Men c (García Muñoz et al 2019), and marginal detections were reported for the small rocky-planet systems in TRAPPIST-1 (Bourrier et al 2017a) and Kepler-444 (Bourrier et al 2017b).…”
Section: Introductionmentioning
confidence: 94%
“…It also showed a non-detection at Lyman-α (Ehrenreich et al 2012). Lyman-α observations of Kepler-444 show variations that might be associated with hydrogen escape from its rocky planets (Bourrier et al 2017b).…”
Section: Introductionmentioning
confidence: 99%